2011
DOI: 10.3892/etm.2011.243
|View full text |Cite
|
Sign up to set email alerts
|

Cancer stem cell-related factors are associated with the efficacy of pre-operative chemoradiotherapy for locally advanced rectal cancer

Abstract: Abstract. pre-operative chemoradiotherapy (crt) is an important neoadjuvant therapy for locally advanced rectal cancer. in the present study, we investigated the factors that influence the efficacy of pre-operative CRT in locally advanced rectal cancer. We divided 50 patients with locally advanced rectal carcinoma treated with pre-operative crt into two groups according to the grade of tumor response to pre-operative crt: low-sensitivity group and high-sensitivity group. as candidates for the prediction of sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Several studies confirmed elevated CD133 expression was associated with resistance to CRT in LARC (57)(58)(59)(60). The status of CD24 was also found to be significantly associated with response to CRT (p = 0.029) (58).…”
Section: Cancer Stem Cell Markersmentioning
confidence: 83%
“…Several studies confirmed elevated CD133 expression was associated with resistance to CRT in LARC (57)(58)(59)(60). The status of CD24 was also found to be significantly associated with response to CRT (p = 0.029) (58).…”
Section: Cancer Stem Cell Markersmentioning
confidence: 83%
“…In CRT-treated patients with colorectal cancer, the upregulation of circulating cancer stem cell markers is vital for clinical parameters including CRT sensitivity (36). Hiroishi et al (37) indicated that prominin-1 and signal transducer CD24 contributed to the sensitivity of preoperative CRT for LARC. In the present study, the GO functional analysis indicated that signaling pathways regulating the pluripotency of stem cells had the highest enrichment of upregulated miRNA-target genes, including PIK3CG and APC2 .…”
Section: Discussionmentioning
confidence: 99%
“…44 Similarly, CD133, another CSC marker, has been reported to correlate with decreased sensitivity to CRT. 45 However, in a study by Sprenger et al evaluating pre-and posttreatment samples from 126 rectal cancer patients, the absolute pretreatment CD133 expression was not associated with response, though the authors noted that patients who had an increase in CD133 after therapy had less tumor regression and worse survival. 46 While the use of CSC-based biomarkers in CRC is still in its infancy, there is exciting potential in terms of predicting treatment efficacy, as well as providing novel therapeutic targets.…”
Section: Cancer Stem Cell Markersmentioning
confidence: 99%